PERCEIVED ORGANIZATIONAL SUPPORT, WORK ENGGEMENT, DAN JOB AUTONOMY: UPAYA STRATEGIS MENINGKATKAN KREATIVITAS - Noerchoidah, Noerchoidah; Nurdina, Nurdina; Latif, Nashrudin; Rossitika, Amanda Rizky; Frisyanto, Balqis Khairunisa (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of perceived organizational support (POS) on the creativity of creative industry employees in Surabaya, with work engagement as a mediator and job autonomy as a moderator. This study used a survey method, collecting data via questionnaires from 165 employees selected through purposive sampling. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach in SmartPLS. The results indicate that POS has a positive and significant effect on work engagement and creativity; work engagement also positively affects creativity and mediates the relationship between POS and creativity. Conversely, job autonomy did not moderate the relationship between work engagement and creativity. The coefficient of determination indicates that the model has moderate explanatory power for creativity and low explanatory power for work engagement. These findings confirm the importance of POS and work engagement as key factors driving employee creativity in the creative industry